Effects of Exercise on Quality of Life in Stroke Survivors: A Literature Review - Georfia Chalkia; Kallistratos Vargi; Adib Kamil Bin Husen (Lentera Perawat, 2025)
Stroke survivors often experience significant impairments in physical, psychological, and social functioning, leading to reduced quality of life (QoL). Exercise has emerged as a promising intervention to enhance recovery, yet its comprehensive effects on QoL remain underexplored. This literature review aims to examine the impact of exercise on QoL in stroke survivors by analyzing its benefits across multiple domains, identifying optimal intervention strategies, and addressing implementation barriers. A systematic search of peer-reviewed studies from 2014–2024 was conducted across major databases, focusing on exercise interventions and their outcomes in stroke rehabilitation. Findings demonstrate that structured exercise programs, including aerobic, resistance, and task-specific training, significantly improve motor function, psychological well-being, and social participation. Caregiver involvement and empowerment-based approaches further enhance adherence and long-term outcomes. However, barriers such as accessibility, motivation, and financial constraints limit widespread implementation. The review concludes that exercise is a vital component of stroke rehabilitation, with multidisciplinary, personalized approaches yielding the best results. Future research should focus on standardized protocols, technology-assisted solutions, and policy changes to improve accessibility and sustainability of exercise-based interventions for stroke survivors.